2011
DOI: 10.1002/pi.3091
|View full text |Cite
|
Sign up to set email alerts
|

Non‐isothermal crystallization of poly(ethylene oxide)/silver nanoplate composites

Abstract: The non-isothermal crystallization of poly(ethylene oxide) (PEO)/silver nanoplate composites was studied using differential scanning calorimetry. The non-isothermal crystallization was analyzed by combining the Avrami and Ozawa equations. It was found that the Avrami exponent for neat PEO ranges from 2.51 to 2.53, whereas it ranges from 2.54 to 3.16 for its composites, indicating that the spherical crystal morphology does not change with the addition of nanoplates. However, the rate determination of crystal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…F(T) can be regarded as the non-isothermal crystallization rate parameter while the lower values indicate higher crystallization rates [27]. According to this method, the plot of ln ϕ versus ln t at a certain relative crystallinity should result in a straight line.…”
Section: Analysis Based On Combined Avrami-ozawa Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…F(T) can be regarded as the non-isothermal crystallization rate parameter while the lower values indicate higher crystallization rates [27]. According to this method, the plot of ln ϕ versus ln t at a certain relative crystallinity should result in a straight line.…”
Section: Analysis Based On Combined Avrami-ozawa Equationmentioning
confidence: 99%
“…Adhikari and Lozano used DSC to investigate the crystallization behavior of PEO/carbon nanofiber systems under nonisothermal conditions and showed that all carbon nanofiber loadings retard the crystallization of PEO [25]. The effect of two-dimensional silver nanoplatelets on the non-isothermal crystallization of PEO has been discussed by Rahmansyah et al [26,27]. They found that the overall crystallization rate of nanocomposites was slower than that of neat PEO and the radius of spherulites was greater.…”
Section: Introductionmentioning
confidence: 95%
“…The Avrami model has been applied to crystallization on cooling by a conversion of the temperature to time scales . Also a combination of Avrami and Ozawa methods has been proposed …”
Section: Resultsmentioning
confidence: 99%